2022
DOI: 10.1055/a-1914-1799
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Enantioenriched Azaborole Helicenes by Chirality Transfer from Axially Chiral Biaryls

Abstract: We report the enantioselective synthesis of azaborole helicenes from enantioenriched axially chiral precursors. The borylation/metal exchange reaction sequence affords target compounds with full transfer of chirality from the corresponding biaryls. Experimental studies provide insights into the configurational stability of the heteroobiaryls and (chiro)ptical properties. The structure of the phenyl-substituted helicene was unambiguously confirmed by single crystal X-ray analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…7,73 In 2023, a breakthrough by Nowak-Król and coworkers disclosed that the asymmetric synthesis of enantiopure azaborahelicens can be manipulated by the cycloborylation of enantioenriched axially chiral 2-phenylpyridine-type biaryls using BBr 3 in the presence of i Pr 2 NEt producing a B,Bdibromo-azaborole platform, which was subsequently reacted with AlMe 3 or AlPh 3 (Scheme 16). 74 This approach makes use of the nitrogen atom which directs the electrophilic aromatic borylation to the ortho-position, enabling a formal C-H functionalization via axial-to-helical chirality transfer. Despite the progress, the development of a general catalytic asymmetric protocol for the preparation of enantiopure azaborahelicens is highly appealing and sought after.…”
Section: Reviewmentioning
confidence: 99%
“…7,73 In 2023, a breakthrough by Nowak-Król and coworkers disclosed that the asymmetric synthesis of enantiopure azaborahelicens can be manipulated by the cycloborylation of enantioenriched axially chiral 2-phenylpyridine-type biaryls using BBr 3 in the presence of i Pr 2 NEt producing a B,Bdibromo-azaborole platform, which was subsequently reacted with AlMe 3 or AlPh 3 (Scheme 16). 74 This approach makes use of the nitrogen atom which directs the electrophilic aromatic borylation to the ortho-position, enabling a formal C-H functionalization via axial-to-helical chirality transfer. Despite the progress, the development of a general catalytic asymmetric protocol for the preparation of enantiopure azaborahelicens is highly appealing and sought after.…”
Section: Reviewmentioning
confidence: 99%
“…We have also demonstrated that the synthesis of azaborole helicenes can be carried out in an enantiospecific fashion by axial-to-helical chirality transfer from enantioenriched axially chiral ligands ( Scheme 3 ). 58 Due to the enhanced rotational freedom of biaryls compared to the target helicenes, the rotation about the chiral axis may proceed in either sense leading to two plausible enantiomerization pathways. One of them is a puckered helicene-type transition state (TS), in which the steric hindrance is produced by N and 2-C atoms.…”
Section: Synthesismentioning
confidence: 99%
“…These problems could be solved by developing efficient protocols for the stereoselective synthesis of different subclasses of boron helicenes, which would be applicable to a broad substrate scope. Except for a few examples of stereoselective synthesis of boron helicenes, including our stereospecific synthesis of laterally extended azaboroles via axial-to-helical chirality transfer, which is, on the other hand, limited by the access to optically active biaryls, 58 this area is yet to be explored.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…[64] More recently, the same group reported the first example of enantiospecific synthesis of BN-doped helicenes starting from axially chiral biaryls (Scheme 8). [65] Scheme 8. First reported example of enantioselective synthesis of B(sp 3 )N-helicenes.…”
Section: Synthesis Of B-doped Helicenesmentioning
confidence: 99%